Klasifikasi Kualitas Udara di Jakarta Pada Bulan Agustus 2024 Menggunakan Algoritma C4.5 - Ayu, Ika Juni Nur; Putri, Nayla Rahmania; Nugraha, Ridho Putra; Febriansyah, Ryan (JDMIS: Journal of Data Mining and Information Systems, 2025)
Air is one of the important factors in human survival besides land and water. Poor air quality will have a negative impact on human health, ecosystem balance and climate change. This study aims to classify air quality in Jakarta in August 2024 using data mining techniques with the C4.5 algorithm. The data analyzed was obtained from the Satu Data Jakarta website published on February 19, 2024, including several measurement parameters, namely pm_sepuluh, pm_duakomalima, sulfur_dioxide, carbon_monoxide, ozone and nitrogen_dioxide. In its implementation, this research uses RapidMiner tools to process and analyze data. The classification results show that air quality in Jakarta during the period can be categorized into two groups, namely unhealthy and moderate, with the majority of measurements falling into the moderate category. The resulting classification model achieved an accuracy rate of 99.35%, indicating that the C4.5 algorithm is very effective in identifying and predicting air quality in Jakarta. This result shows that most of the air quality measurement data in Jakarta is still in a category that meets good air quality standards